Insights into heat management of hydrogen adsorption for improved hydrogen isotope separation of porous materials. (20th June 2021) - Sun, Nan; Li, Pei-Long; Wen, Ming; Song, Jiang-Feng; Zhang, Zhi; Yang, Wen-Bin; Zhou, Yuan-Lin; Luo, De-Li; Zhang, Quan-Ping
Graphical abstract: . Highlights: Heat management in porous material promotes hydrogen isotope separation. Enhanced thermal conductivity leads to improved hydrogen adsorption. High thermal conductivity is more beneficial to D2 than H2 adsorption. Enhanced thermal conductivity contributes to low energy consumption. Abstract: Separating high-purity hydrogen isotopes from their mixture still remains a huge challenge due to almost the identical physicochemical properties. Much importance has been attached to tune microstructure of porous materials, while heat management during hydrogen isotope separation tends to be ignored. Herein, a porous material 5A molecular sieve (5A) is mixed with graphene (GE) under ball grinding to enhance its thermal conductivity for hydrogen isotope separation. The thermal conductivity increases from 0.19 W m −1 K −1 of neat 5A, 0.75 W m −1 K −1 of 5A/GE2 (2 wt% GE) to 1.23 W m −1 K −1 of 5A/GE8. In addition, introducing GE into 5A promotes hydrogen adsorption and D2 /H2 adsorption ratio. 5A/GE2 shows the highest D2 adsorption capacity (5.40 mmol/g) and the largest D2 /H2 adsorption ratio (1.07) among the composites. It also displays a high efficiency of heat transfer that contributes to a low energy consumption due to the shortened cycle time during hydrogen isotope separation. This work offers new insights into material design for improved hydrogen isotope separation, which is greatly crucial to scientific and industrial applications, such as fuel self-sustaining in fusion reactors.